A Cage Is a Cage, Unless You Educate. Rhetoric Negatively Impacts Support for a Novel Housing System for Laying Hens Unless the Public Are Educated - Nolan, Huw R. J.; Hemsworth, Lauren M.; Power-Geary, Jennifer A.; Taylor, Peta S. (Frontiers in Veterinary Science, 2022)
It has been proposed that terminology on commercially available eggs can impact the manner in which the eggs are discussed and ultimately consumer support. In this paper, we tested if the label of ‘furnished cage’ eggs is a barrier for its support in Australia. Furthermore, we examined if educational interventions could change support and the way furnished cages were discussed. Survey participants (n =1157) were recruited by a stratified random sample of Australian adults. The participants were surveyed on their demographics, attitudes towards the poultry industry and animal welfare, and their egg buying behaviour. Participants were randomly assigned to one of four treatment groups; two control groups and two educational groups. Participants were shown one of three videos, the control groups were shown a video with general information about chickens, the educated groups were shown one of two almost identical videos that educated them on aspects of the egg-laying industry in Australia, and the welfare implications of different housing systems including furnished systems. The only difference between the two educational videos was the name given to the furnished housing system; one group was introduced to furnished cages, the other was introduced to furnished coops. Educated participants were more likely to support furnished eggs and discuss them more positively than the control groups. When asked to discuss their support for furnished systems, control group participants exposed to the term cage were more likely to discuss the impacts of caged environments than the other treatment groups. The study suggests any negative impacts of housing system terminology can be mitigated through educational interventions.